The BA in History: An Hermeneutic place to think about the meaning of the classroom - Moura, Rosana Silva de (Education Policy Analysis Archives, 2013)
This essay addresses some issues related to the degree in History from contributions of HG Gadamer's philosophical hermeneutics and W. Dilthey. Highlights of the space history lesson from a perspective that considers how privileged locus to think of possible meanings formation of historical consciousness. From this approach reconfigures itself the place of undergraduate universities in the scenario that, in Brazil, have privileged research at the expense of teacher education, including delinking research and teaching. Soon, the questions that remain concern: Why do research in history? To whom it is directed? What is its function? The study helps to think of the inseparable link between teaching and research, placing a degree in History as a place to think hermeneutic senses of a class and its historical productivity, as taught HG Gadamer.